THE IMPROVEMENT CRITICAL THINKING SKILLS OF STUDENTS WITH EMPIRICAL INDUKTIVE LEARNING CYCLE - rika septianingsih; nina kadaritna; ila rosilawati (Jurnal Pendidikan dan Pembelajaran Kimia, 2013)
The aim of this research was to describe effectiveness of empirical inductive learning cycle model in improving of critical thinking skills of students in sub skills of analyzing arguments.  Indicators of critical thinking skills studied were identifying conclusions and seeing similarities and differences. Population was all 170 students of Grade XI State Senior High School 3 in Kotabumi. Samples were 34 students in XI Sains 2 class and 34 students in XI Sains 3 class that have equal academic abilities. This was a quasi experiment research using non equivalent control group design. Effectiveness of learning with empirical inductive learning cycle model was measured based on significant gain improvements of skill in analyzing arguments. The results showed that average value of n-Gain of skill in analyzing arguments in experiment and control classes were 0.62 and 0.42 respectively. The hypothesis result test showed that class which used empirical inductive learning cycle model had higher skill in analyzing arguments than class with conventional learning model. This indicated empirical inductive learning cycle model was effective to improve critical thinking of students in the acid base matery in state senior high school 3 in Kotabumi.Keywords: empirical inductive learning cycle, critical thinking skills of students